PENGEMBANGAN BUKU AJAR DIGITAL PAI BERBASIS INTEGRATIF SAINS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA - Rina Nirwana; Riswanto Riswanto; Alimni Alimni (Universitas Negeri Padang, 2025)
This study aims to develop a digital textbook for Islamic Religious Education (PAI) based on integrative science that is valid, practical, and effective in enhancing the creative thinking skills of students at SMPIT Al-Marjan Nusa Indah, Bengkulu City. The research employed a Research and Development (R&D) approach using the ADDIE development model. The data sources in this study consisted of both qualitative and quantitative data. Qualitative data were obtained from expert reviews and suggestions provided by media experts, content experts, PAI teachers, and students. Meanwhile, quantitative data were derived from expert validation assessments and student response questionnaires. The results of this research and development indicate the following: (1) The development of the digital Islamic Religious Education textbook was deemed valid by the validators, as evidenced by the validation scores from the content expert (91.4%), media expert (94.2%), language expert (90%), and subject teacher expert (93%), all of which fall under the